Analysis of genetic diversity of Centella asiatica using SSR markers - Sakthipriya, M.; Vishnu, S.S.; Sujith, S.; Kumar, P. Rajesh; Sabu, K K (International Journal of Applied Sciences and Biotechnology, 2018)
Genetic diversity represents the heritable variation within and between populations of organisms. A better understanding of genetic diversity and its distribution is essential for its conservation and use. In this study the genetic diversity analysis was performed in 30 accessions of Centella asiatica (L.) Urb. using 10 SSR markers. C. asiatica is a tropical medicinal plant from Apiaceae family native to Southeast Asian countries. It is among the top herbs in the category of anti-aging and CNS drugs used worldwide. The whole plant and aerial parts are used widely in traditional and alternative medicines due to its ample pharmacological activities. The molecular screening through microsatellite markers showed low polymorphism (0.019) between the samples analyzed. Further studies, including the effect of environmental factors, genetic composition or possibility of inbreeding, are required to analyze the probable reason for the low variability exists in the species.Int. J. Appl. Sci. Biotechnol. Vol 6(2): 103-109